Газодинамічні процеси у вузлах високообертового пневмошпинделя на аеростатичних опорах із турбінним приводом, призначеного для застосування в багатокоординатному технологічному обладнанні з паралельними кінематичними структурами - Струтинський, С. В. (НТУ "ХПІ", 2015)
Розглянуто багатокоординатне технологічне обладнання у вигляді верстата–робота із паралельними кінематичними структурами. Наведена конструктивна схема розробленого високо обертового пневмошпинделя. Він має спеціальні аеростатичні опори підвищеної несучої здатності та турбінний привод обертання. Визначено особливості газодинамічних процесів у вузлах пневмошпинделя при наявності його просторового переміщення. Дія додаткових об’ємних сил врахована у рівняннях Нав’є–Стокса, які записані для випадку наявності прискорень Коріоліса в рухомому текучому середовищі. Одержана система диференціальних рівнянь використана для досліджень течії повітря в щілинах аеростатичних підшипників та в осьовій пневмотурбіні.

The multi–processing technological equipment in the form of robotic machine–tool with parallel kinematic structures was reviewed. The constructive scheme of high–speed pneumatic spindle was shown. It has special aerostatic bearings with highload capacity and turbine rotational drive. The aerostatic bearings are placed on the surfaces of spindle tubularprojections and interactwith the tubular projections of the housing. The features of gasdynamic processes in pneumatic spindle nodes during its spatial displacement are identified. The additional volume forces are taken into account in the Navier–Stokes equations in the case of Coriolis acceleration in the moving fluid presence. The resulting system of differential equations is used to study the flow of air in the crevices of aerostatic bearings. The features of the air flow in the gaps caused by the Coriolis force are identified. The possibility of flowing asymmetry in cracks and the possible ways to compensate the negative impact of flowing asymmetry on the characteristics of aerostatic bearings are listed. The features of air flow in the axial pneumatic turbine.
Gasdynamic processes in high–speed pneumatic spindle nodes on aerostatic bearings of the turbine drive designed for use in a multi technological equipment with parallel kinematic structures
Keywords: течія повітря; переносний рух; розподіл швидкостей; pneumatic spindle; aerostatic bearing; turbine; air flow